Phenolic content and profile of olive fruits Impact of contrasting thermal regimes in non-Mediterranean growing environments - Pierantozzi, Pierluigi; Torres, Myriam Mariela; Contreras Valentin, Ana Cibeles; Stanzione, Vitale; Tivani, Martin; Gentili, Luciana; Mastio, Valerio; Searles, Peter Stoughton; Brizuela, Magdalena; Fernandez, Fabricio; Toro, Alejandro Alberto; Puertas, Carlos Marcelo; et al. (Elsevier, 2025)
The content of phenolic compounds in olive fruits is a matter of interest, not only because of their contribution to olive oil quality but also to their beneficial effects on human health. While some studies mention genetic and agronomic factors affecting the olive fruit phenolic composition, there is still a lack of information on the role of the environmental growth temperature. This study addresses the impact of different thermal regimes on hydrophilic phenol contents from two olive cultivars (Arbequina and Coratina) growing at several environments in Argentina. The variability associated with the growing environment was significant for all compounds analyzed; lower total phenol contents were associated with warmer environments. Verbascoside and oleuropein aglycone were the compounds reflecting more clearly this general tendency; their contents were approximately 2–3 fold lower in the warmest than in the coldest environment. To assess relationships between thermal records and phenolic contents, various models were tested; those including the thermal time showed the best fit. In general, data from cv. Arbequina showed better fit than those from cv. Coratina. As a summary, a genotype-associated response is suggested whereby the tested cultivars would have the ability to accumulate higher amounts of total and specific phenols when grown in cooler environments.